Feasibility of transnasal endoscopy in screening for esophageal and gastric varices in patients with chronic liver disease - de Faria, Anderson Antônio; Dias, Carlos Alberto Freitas; Dias Moetzsohn, Luciana; de Castro Carvalho, Silas; Ferrari, Tereza Abreu; Nunes Arantes, Vitor (Endoscopy International Open, 2017)
Background and study aims Screening for esophageal and gastric varices is indicated for patients with portal hypertension or cirrhosis. Typically, conventional endoscopy is used; however, the need for sedation increases the costs and risks, especially in cirrhotic patients. Use of transnasal endoscopy with an ultrathin endoscope enables study of the upper gastrointestinal tract without the need for sedation. The objective of this study is to evaluate the feasibility of transnasal endoscopy in screening for esophageal and gastric varices in patients with chronic liver disease.Patients and methods This was a prospective study in which transnasal endoscopy was carried out in patients with cirrhosis or portal hypertension who had indications for screening of esophageal and gastric varices. The following variables were evaluated: demographical data, duration of procedure, patient tolerance and acceptance, adverse events (AEs), endoscopic findings and interobserver agreement related to portal hypertension alterations (kappa index).Results A total of 50 patients entered the study. The most common cause of liver disease was chronic viral hepatitis (66 %). Among the cirrhotic patients, most of the patients were Child-Pugh A (74 %). In 5 patients (10 %), nasal intubation was not possible. Two patients (4 %) experienced minor epistaxis. Tolerance was excellent or good in 92 % according with a visual analogic scale. In 16 patients (32 %), esophageal varices were detected and in 2 patients (4 %) gastric varices were detected. The mean duration of the procedure was 7 minutes. Conclusions Transnasal endoscopy is feasible, effective and well tolerated for screening of esophageal and gastric varices in patients with chronic liver disease. It can be performed in outpatient clinics safely and without the use of sedation.